Acoustic emission precursor information of rock failure under true triaxial loading and unloading conditions - Liu, Sijie; Zheng, Haijun; Chen, Guoqing; Hu, Yitao; Meng, Kai (Frontiers in Earth Science, 2023)
Rock failure generally leads to serious consequences, and it is significant to obtain the precursor information prior to failure using associated techniques. Acoustic emission (AE) is one of the indispensable methods for disaster warning of hard and brittle rock. Acoustic emission detection technology can effectively monitor real-time information about changes in the rock interior and predict the process of rock damage failure. To probe the relationship among the AE precursor information of red sandstone under different intermediate principal stresses, an experimental study was conducted by us to examine the alterations in AE parameters during the failure of red sandstone under both loading and unloading circumstances. The study shows that the ringing count rate and absolute energy versus time curves are divided into four stages, namely quiet, frequent, sudden increase and decline periods. The cumulative count curve is also divided into four phases: pre-unloading period, post-unloading period, sharp increase period, and decrease period. With the rise of the intermediate principal stress, the ringing count rate and energy exhibited during the frequent period of AE demonstrate a consistent increase, with a larger increase in the maximum value and a smaller increase in the average value. In addition, the peak value of AE signals during failure also increases accordingly. The occurrence moment and clarity of the frequent period determine the reliability and priority of the information related to the rock's failure precursor; moreover, the reliability and priority of the AE precursor information will increase with the increase of the intermediate principal stress. After comparison, it is found that the AE precursor information occurs prior to the thermal infrared precursor information.